Local Government Own-source Revenue and General Allocation Funds on Capital Expenditure: Economic Growth as Moderating Variable - Mulyana Mulyana; Muhammad Din; Mustamin Mustamin; Andi Mattulada Amir; Fikry Karim; Betty Betty (Arthatama: Journal of Business Management and Accounting, 2022)
This article aims to analyze the influence of locally-generated revenue in local government in Indonesia and general allocation funds on capital expenditure with economic growth as moderating variable. This examination involves auxiliary information such as the 2015-2019 local budget report. The number of tests in this review was 29 areas from 34 territories in Indonesia. This review utilizes the Partial Least Square (PLS) examination with the assistance of WarPLS 7.0 programming. The results showed that neighborhood income positively affects capital use. General allocation funds positively affect capital expenditure. Moreover, financial development directs or strengthen local government own-source income through capital expenditure.